Icaritin Induces Anti-tumor Immune Responses in Hepatocellular Carcinoma by Inhibiting Splenic Myeloid-Derived Suppressor Cell Generation - Tao, Huimin; Liu, Mingyu; Wang, Yuan; Luo, Shufeng; Xu, Yongquan; Ye, Bin; Zheng, Limin; Meng, Kun; Li, Lian (Frontiers in Immunology, 2021)
Recent studies have demonstrated that splenic extramedullary hematopoiesis (EMH) is an important mechanism for the accumulation of myeloid-derived suppressor cells (MDSCs) in tumor tissues, and thus contributes to disease progression. Icaritin, a prenylflavonoid derivative from plants of the Epimedium genus, has been implicated as a novel immune-modulator that could prolong the survival of hepatocellular carcinoma (HCC) patients. However, it is unclear whether icaritin achieves its anti-tumor effects via the regulation of MDSCs generated by EMH in HCC. Here, we investigated the anti-tumor potential of icaritin and its mechanism of action in murine HCC. Icaritin suppressed tumor progression and significantly prolonged the survival of mice-bearing orthotopic and subcutaneous HCC tumors. Rather than exerting direct cytotoxic activity against tumor cells, icaritin significantly reduced the accumulation and activation of tumoral and splenic MDSCs, and increased the number and activity of cytotoxic T cells. Mechanistically, icaritin downregulates the tumor-associated splenic EMH, thereby reducing the generation and activation of MDSCs. The inhibitory effects of icaritin on human MDSCs in vitro were verified in short-term culture with cord-blood derived hematopoietic precursors. Furthermore, icaritin synergistically enhanced the therapeutic efficacy of immune checkpoint blockade therapy in HCC mice. These findings revealed that icaritin dampens tumoral immunosuppression to elicit anti-tumor immune responses by preventing MDSC generation via the attenuation of EMH. Thus, icaritin may serve as a novel adjuvant or even a stand-alone therapeutic agent for the effective treatment of HCC.